Piezo ICSI versus conventional ICSI in human assisted reproduction: A scoping review of laboratory, clinical, and neonatal outcomes - Van Thinh Ngo; Thi Thuy Dung Le; Thanh Luan Nguyen; Thi Thuy Tran; Thi Huyen Nhung Dang (Asian Pacific Journal of Reproduction, 2026)
Objective: To systematically map and evaluate the laboratory, clinical, and neonatal outcomes of Piezo-assisted intracytoplasmic sperm injection (Piezo ICSI) compared to conventional ICSI in human assisted reproduction. Methods: A scoping review was conducted according to PRISMA-ScR guidelines. A systematic search of PubMed and Google Scholar was performed for studies published up to March 11, 2026, that compared Piezo ICSI with conventional ICSI and reported at least one laboratory, clinical, or neonatal outcome in humans. Results: Ten studies were identified, including one randomized controlled trial and nine non-randomized studies. Piezo ICSI generally showed improved laboratory outcomes, specifically improved oocyte survival and fertilization rates, with some evidence of enhanced embryo development. Clinical outcomes were less consistent: while several studies suggested improved clinical pregnancy and live birth rates, others, including a multicenter trial, reported no statistically significant benefits. Only three studies reported neonatal data, which showed no increase in adverse outcomes despite the limited scope. Conclusion: Current evidence suggests that Piezo ICSI offers reproducible laboratory advantages, particularly for women of advanced maternal age or with poor prognosis. However, its definitive clinical and neonatal impacts remain inconclusive. Further large-scale, well-designed multicenter trials with long-term follow-up of offspring are required before recommending Piezo ICSI for routine clinical practice.